Chukwu Ome-nala (Hekima Review, 2016)
Josef, the carpenter, works, yet himself doubting:“I can’t believe I made this” he says, hammering. To his shop, Anikenwa2, the sage, proceeds, marvelingAt the low tripod-stand-stool by Joseph’s cra forming,Anikenwa kneels, feeling the stool, touching